THE COURT OF GENERAL QUARTER SESSIONS OF THE PEACE: LOCAL ADMINISTRATION IN PRE-MUNICIPAL UPPER CANADA - Wilson, James K. (My University, 1991)
Between 1800 and 1832 virtually all aspects of local administration in Upper Canada were overseen by those men appointed to the office of Justice of the Peace. During this era the Justices of the Peace sitting in the Court of General Quarter Sessions of the Peace accumulated. the vast majority of administrative and judicial powers granted by the Colonial Government to oversee local settlement. In the District of Johnstown, prior to its spectacular growth between 1816 and 1820, the monopoly of power which the Magistrates were granted allowed them to effectively administer to the administrative and judicial needs of the settlers in the District. However, as the population of the colony grew and administration became more time-consuming and complex, an unwieldy number administrative tasks were placed upon the shoulders of the Justices of the Peace. By 1832 the system of local government by the Magistrates had virtually collapsed. Through an analysis of the office of the Justice of the Peace, its role in local government, and its accomplishments in the early years of Upper Canada, this dissertation identifies some of the basic reasons which led to the demise of the pre-eminent position of Justices of the Peace in local administration and its replacement with elected Boards of Police in 1832. This analysis reveals that the traditional belief of Justices of the Peace as self-glorifying members of the colonial elite rather than effective instruments of local government is oversimplified. If fact, there existed a determined core of Working Justices who rose beyond what was expected of them between 1800 and 1832 to provide an effective form of local government. That the Working Justices were eventually unable to fulfill the needs of their office is largely not a reflection of their abilities, but rather of circumstance.
Keywords: History; History